The Influence Of Trust And Social Media Regarding The Decision To Purchase The Al-Kinan Collection Shop (Survey Of Al-Kinan Collection Shop Consumers Via Online Media) - Jamilah, Dedeh; Pauzy, Depy Muhamad; Risana, Dudu (Universitas Dehasen Bengkulu, 2024)
This research aims to determine the influence of trust and social media simultaneously on purchasing decisions at the Al-Kinan Collection store. The partial influence of trust and social media on purchasing decisions at the Al-Kinan Collection store. The method used in this research is causal descriptive with a quantitative approach. With a research sample of 100 people as respondents from Al-Kinan Collection shop consumers. The data used is primary data. The analytical tool used in this research is multiple linear regression using the SPSS version 25 application. The results of simultaneous testing of trust and social media have a significant effect on purchasing decisions. Partially, the trust variable has a significant effect on purchasing decisions, as well as the social media variable partially has a significant effect on purchasing decisions.